Inclusive business in the Asia Pacific Economic Cooperation. (Metro Manila, Philippines Asian Development Bank, 2018)
APEC,as a regional organization of economies in the Americas and in Asia, is well suited to promote inclusive business (IB) as a new approach to make economic growth more sustainable and more inclusive. While agreements in APEC are mainly related to trade, the governments agenda in the region for a more inclusive economic development widen the discussions among APEC economies to promote consensus on new strategic economic topics. IB and investing to create impact on people and the environment is one such new and emerging topic.The publication discusses the market potentials, constraints, and necessary policy instruments for an enabling environment for inclusive business. A profile of inclusive business initiatives, the overview of the base of the pyramid market size, and the inclusive business ecosystem in each APEC economy as well as a recommended a framework to guide future work on inclusive business under the APEC regional economic cooperation agenda are also included in this report.
Keywords: Public-private sector cooperation -- Asia -- Finance; Industry and State; Electronic books